2015
DOI: 10.1016/j.jbiomech.2014.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative contractility: The role of stress fibres in the regulation of cell-cell junctions

Abstract: We present simulations of cell-cell adhesion as reported in a recent study [Liu et al., 2010, PNAS, 107(22), 9944-9] for two cells seeded on an array of micro-posts. The micro-post array allows for the measurement of forces exerted by the cell and these show that the cell-cell tugging stress is a constant and independent of the cell-cell junction area. In the current study, we demonstrate that a material model which includes the underlying cellular processes of stress fibre contractility and adhesion format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Upon exposure to TDNs, chondrocytes may send complicated biological signals to make adjustments of microtubules and the expression of relevant genes. Computational models have revealed that cellular microtubule compression force may influence stress fibers . Therefore, after 24 h of exposure to TDNs, chondrocytes displayed a relevant round morphology, which is similar to the chondrocyte phenotype and what is more, the relevant genes related to the Notch signaling pathway was downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Upon exposure to TDNs, chondrocytes may send complicated biological signals to make adjustments of microtubules and the expression of relevant genes. Computational models have revealed that cellular microtubule compression force may influence stress fibers . Therefore, after 24 h of exposure to TDNs, chondrocytes displayed a relevant round morphology, which is similar to the chondrocyte phenotype and what is more, the relevant genes related to the Notch signaling pathway was downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that the elastic modulus of MSCs is significantly influenced by the cytoskeleton (Titushkin and Cho, 2007). Adhesion junctions transmit mechanical forces such as cytoskeletal tension between cells (Ganz et al, 2006; Maruthamuthu et al, 2011) and are strengthened and stabilised by interaction with the cytoskeleton (Pittet et al, 2008; Liu et al, 2010; Hong et al, 2013; Ronan et al, 2015). In this study we demonstrate that the cytoskeleton/adhesion junction relationship is reciprocal; adhesion junctions also influence stress fibre formation and mesensphere mechanical behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation in RhoA activity can initiate high engagement of myosin with actin filaments to yield dense stress fibers, which can promote clustering of cadherin proteins and transmit high tension to cadherin bonds 17 , 18 . Mechanical stress regulates cadherin turnover at cell junctions 19 and directly increases the size of cell-cell adhesions 20 , 21 . RhoA activation has also been shown to induce junction contraction and strengthening 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%